SCRUM: From rugby to teamwork in higher education - Sobral, Sónia Rolland (2018)
Rugby is a sport admired for its particularities and teachings for life in society. Despite being a collective sport with physical contact, it has a code of ethics and a set of values ​​that differentiate it from other sports: Respect, Integrity, Passion, Solidarity and Discipline. A Rugby player is expected to be a team worker, have courage and loyalty. It is an inclusive sport: 15 players each with specific responsibilities and different functions. There are places for everyone: the small /agile, tall, fast, strong or the combative can be a 9, 4, 15, 1 or 6 respectively. Each element has to know the rules well and do their part of the game, always following the indications of the coach. A player has to encourage team-mates: everyone has their importance in the whole. Each team wants to advance on the field and score points. One of the ways to restart the game is the scrum: can occur when a player drops the ball forward or makes a forward pass, for instance. The teams have a maximum of 30 seconds to form. After the referee's orders for "crouch, bind and set" that the ball may be introduced by the scrum half of the non-offending team on the floor by the center line until it leaves the tunnel formed by the first rows and skidded by the feet of the hooker. There are many other specifics that are important for scrum like the variation of the modality: rugby XV 8, sevens 3, training levels (some don't exist, or form with 5 or 7). The principles of rugby scrum have been used for project management, particularly in software development, which has been widely studied. The items initially intended for a project are defined but may change. The scrum team are usually 6/10 people, one is the product owner and another the scrum master. The product backlog is divided into n sprints, each containing a sprint backlog defined at the beginning of each sprint in a sprint planning meeting where the entire team must be present and where the Product Owner will be the one who prioritizes the tasks to be included in this list. There must be a Daily Scrum every day where each team member presents what has been done, possible problems and takes their commitments for the day. At the end of each sprint, a Sprint Review Meeting is held to present the implemented features, the Sprint Retrospective is updated, the Release Burndown Chart is updated and planning is started for the next sprint. As in Rugby, the teams are small, there is a commitment to the position of each in the group, the motivational factor is very important and the rules are to be met without any malicious discussion between the various elements. Each one knows that for a sprint to succeed everyone has to be able to meet the stipulated for "their position". Teamwork is often used as a form of application of knowledge and evaluation in university. There's several teaching experiences using scrum principles with clear advantages: delivery times, group motivation and commitment/accountability of each element, as well as records of work. Some of these experiences include the use of eduscrum which is an application of the methodology to the teaching. This article intends to evaluate some of these documented experiences, drawing conclusions for the success of using scrum as a basis for teamwork in units as introduction of computer programming in higher education to decrease the abandonment rate and the failure rate.